Histological Effects of Saccharomyces Boulardii Probiotic in Some Mice Organs Infection with Salmonella Typhimurium - Hanan Abdullah Ali Al-Shammary (Journal of Global Pharma Technology, 2018)
Background and Objective: Saccharomyces Boulardii, Eukaryotic probiotic it was unable to proven therapeutic efficacy. This study leads to evaluate the protective effect of three types of probiotic yeast Saccharomyces Boulardii in the tissues of some internal organs of laboratory mice before and after infection with pathogenic bacteria Salmonella Typhimurium. Materials and Methods: Three types of yeasts were used ,Local Iraqi Isolate (Local Saccharomyces Boulardii) LSb ,Mutant Iraqi Isolate (Mutant Saccharomyces Boulardii) MSb and commercial strain (Commercial Saccharomyces Boulardii) CSb. Forty male white mice were divided into 4 groups , Each group included 10 mice: control, MSb, CSb and LSb ,dosed with 0.2 ml/day for 28 days of yeast inoculums except control treatment fed on the standard diet, half number of animals in each group were sacrificed for histological examination of some organs (liver, spleen and intestine),the remaining mice were infected with 0.2ml of S. Typhimurium daily for 8 days , and sub-treated have been derived: Control + St, MSb + St, CSb + St and LSb + St. the histological examination of the indicated organs was performed .Results: Histological indicators of internal organs (liver ,spleen and intestine) of the groups MSb, LSb and CSb, shown that no necrosis or clear lesion or inflammatory sign in those organs .In addition ,histological examination of infected St +control group shown necrosis of hepatocytes , congested central vein and dilated of sinusoids of the liver , necrosis in the lymphoid tissue and inflammatory cells infiltration in the white pulp of the spleen , while the changes in the intestine shown inflammation cells infiltration in the lamina properia and erosion of epithelial cells , compared with the positive effects of MSb + St, CSb + St, and LSb + St in reducing necrosis ,inflammation and cytotoxic effects of S. typhimurium, but the MSb + St group was the best .Conclusion: Mutant Iraqi isolate was the efficient in protective the tissues of (liver, spleen and intestine of animals after infections with S. Typhimurium bacteria .Keywords: Probiotics, Saccharomyces Boulardii, Mutagenesis, Salmonella Typhimurium, Histopathological changes.